The raven - Vidal, Lucas (20th Century Fox Home Entertainment, 2012)
"Baltimore 1849. While investigating a horrific double murder, police detective Emmett Fields ... makes a startling discovery: the killer's methods mirror the twisted writings of Edgar Allan Poe ... . Suspecting Poe at first, Fields ultimately enlists the writer's help to stop future attacks. But in this deadly game of cat and mouse, the stakes are raised with each gruesome slaying as the pair races to catch a madman before he brings every one of Poe's shocking stories to chilling life"--Container.